Pengaruh Konsentrasi Susu Skim Terhadap Karakteristik Minuman Probiotik Sari Buah Terung Belanda (Solanum betaceaum Cav.) Terfermentasi Dengan Lactobacillus rhamnosus SKG34 - Anggreni Nainggolan, Novita Aristha; Nocianitri, Komang Ayu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p11, 2021)
This research was conducted to determine the effect of skimmed milk concentration on characteristic of fermented tamarillo (Solanum betaceaum Cav.) probiotic juice with Lactobacillus rhamnosus SKG34 and the concentration of skimmed milk that produced the best characteristic. This research used a Completely Randomized Design (CRD) with factor of skimmed milk concentration that consists of 6 levels (0%, 2 %, 4%, 6%, 8%, 10%). Each treatment was repeated 3 times resulting 18 experimental units. The data were analyzed by Analysis of Variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT). The results showed that skimmed milk concentration had a significant effect to total LAB, total sugar, hedonic of color, score of color, and overall acceptance. The concentration of 2% skimmed milk produced the best characteristic of fermented tamarillo (Solanum betaceaum Cav.) probiotic juice with total LAB 8,50 x 109 CFU/ml, total sugar 6,54%, total acid 0,56%, pH 3,72, preferred dark orange color, slightly likeable aroma, preferred sour and slightly sweet taste, and preferred overall acceptance.